2018
DOI: 10.1117/1.nph.5.3.035002
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of pathological features in Alzheimer’s disease brain tissue with a large field-of-view visible-light optical coherence microscope

Abstract: . We implemented a wide field-of-view visible-light optical coherence microscope (OCM) for investigating ex-vivo brain tissue of patients diagnosed with Alzheimer’s disease (AD) and of a mouse model of AD. A submicrometer axial resolution in tissue was achieved using a broad visible light spectrum. The use of various objective lenses enabled reaching micrometer transversal resolution and the acquisition of images of microscopic brain features, such as cell structures, vessels,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 67 publications
(107 reference statements)
1
33
0
Order By: Relevance
“…PS-OCT visualizes amyloid-beta plaques based on their optical scattering and birefringent properties [33][34][35][36]. Previous studies mainly exploited the hyperscattering characteristics of plaques and only one report investigated the birefringent characteristics of neuritic plaques using PS-OCT [19].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…PS-OCT visualizes amyloid-beta plaques based on their optical scattering and birefringent properties [33][34][35][36]. Previous studies mainly exploited the hyperscattering characteristics of plaques and only one report investigated the birefringent characteristics of neuritic plaques using PS-OCT [19].…”
Section: Discussionmentioning
confidence: 99%
“…Several recent reports have demonstrated that amyloid-beta plaques in both human and mouse brain tissue can be visualized using either conventional OCT, PS-OCT [19,[32][33][34][35][36] or other functional extensions such as spectroscopic OCT [32] or directional OCT [36]. Label-free imaging of cerebral amyloid-beta plaques has been achieved using extended-focus optical coherence microscopy (OCM) in the near infrared range at 800 nm [34].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such evaluations along with spectroscopic studies might help elucidate the most optimal clearing conditions/formulas for particular organs of interest . Optical coherence microscopy coupled with CLARITY‐processed brain facilitated detection of Congo red–stained amyloid‐beta plaques in an animal model of Alzheimer's disease . Interestingly, only one day of optical clearing doubled the penetration depth (100 µm vs 200 µm, Figure ).…”
Section: Approaches To Tocmentioning
confidence: 99%
“…b–d) 2 days of SWITCH brain clearing doubles imaging depth (b) and decreases both mean OCM amplitude (c) and mean global attenuation (d) as normalized to noncleared tissue (shaded bands represent standard deviations). a) Reproduced under the terms of the CC‐BY Creative Commons Attribution 3.0 Unported license ( https://creativecommons.org/licenses/by/3.0/) . Copyright 2018, The Authors.…”
Section: Approaches To Tocmentioning
confidence: 99%